Hacia una complexión del discurso intercultural en planes de estudio de educación básica - Malaga-Villegas, Sergio Gerardo (Universidad de Costa Rica, 2019)
This essay analyzes intercultural discourse in the curriculum of Mexico’s basic education. Focuses on the curricula published in this century (preschool 2004, secondary school 2006, elementary school 2009, Integrated Reform of Basic Education 2011, and Educational Model for Basic Education 2017). This constellation of meanings was referred as the institutionalized intercultural discourse. The main argument is that the ideal of Mexico’s Secretariat of Public Education, as condensed in these curricula, tend to be reduced and exclusionist with respect to the field of knowledge of intercultural education at the national level. In organizational terms, this essay is located within the framework of a brief state of knowledge, following with the analysis of intercultural discourse in the indicated curricula, and it concludes with suggestions for continuing the discussion.